Underage Marriage between Purpose and Destiny - Al-Falahi, Muneef Sharyan Ahmed (Journal of Islamic Sciences, 2023)
The research aims to clarify the concept of marriage of minors and its ruling in Sharia and law and linking it to purposes and destiny clarifying the marriage of minors and the difference between a minor and a minor, Ruling on the marriage of minors between Sharia and law, Linking the purposes of marriage to its consequences and applying it to the marriage of minors. The researcher concluded that the marriage of minors is permissible and legitimate, and the contract for minors is valid, but the first failure to marry minors does not achieve the purpose for which the marriage was initiated, and the health, psychological, and social effects it entails.
Keywords: Marriage; Underages; Purpose; Destiny